Final answer:
To express the quadratic function f(x) = 2x^2 + 4x + 3 in standard form, complete the square to get f(x) = 2(x + 1)^2 - 5, which reveals the vertex of the parabola at (-1, -5).
Step-by-step explanation:
Expressing a Quadratic Function in Standard Form
To express the quadratic function f(x) = 2x^2 + 4x + 3 in standard form, also known as vertex form, we need to complete the square. The standard form of a quadratic function is typically written as f(x) = a(x-h)^2 + k, where (h, k) is the vertex of the parabola formed by the graph of the quadratic equation.
Here's how we can rewrite the given quadratic function:
- Divide the coefficient of the x term by 2, which is 4/2 = 2, and then square it to get 4.
- Add and subtract this value inside the parentheses to complete the square: f(x) = 2(x^2 + 2x + 4 - 4) + 3.
- Rewrite the equation by grouping the perfect square trinomial and combining the constants: f(x) = 2((x + 1)^2 - 4) + 3.
- Finally, distribute the coefficient and combine like terms to complete the process: f(x) = 2(x + 1)^2 - 5.
In this form, it is clear that the vertex of the parabola is at (-1, -5).